THE SYMBOLISM OF FLOWERS IN LOUISE GLÜCK’S THE WILD IRIS: AN ECOCRITICAL READING - Zahro Qodirova Zafarovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: Flowers play a central role in Louise Glück’s The Wild Iris, functioning as symbols of life, death, renewal, and the relationship between humans and nature. From an ecocritical perspective, these floral images challenge anthropocentric views by presenting plants as living voices rather than decorative elements. This article examines the symbolism of flowers in selected poems from The Wild Iris through close textual analysis. It argues that Glück uses flowers to express ecological awareness and to emphasize the interconnectedness of human and non-human life. The study concludes that floral symbolism is fundamental to the collection’s ecopoetic vision and its ethical understanding of nature.